Termination of pupal diapause in the pine processionary moth Thaumetopoea pityocampa. (2nd February 2019) - Salman, Md Habibur R.; Giomi, Folco; Laparie, Mathieu; Lehmann, Philipp; Pitacco, Andrea; Battisti, Andrea
Abstract: Diapause development is a complex process involving several eco‐physiological phases. Understanding these phases, especially diapause termination, is vital for interpreting the life history of many insect species and for developing suitable predictive models of population dynamics. The pine processionary moth is a major defoliator of pine and a vertebrate health hazard in the Mediterranean region. This species can display either univoltine or semivoltine development, with a pupal diapause extending from a few months to several years, respectively. Although the ecological and applied importance of diapause is acknowledged, its physiological regulation in either case remains obscure. In the present study, we characterize pre‐termination, termination and post‐termination phases of pupae developing as univoltine or remaining in prolonged diapause. Changes in metabolic activity are monitored continuously using thermocouples, comprising a novel method based on direct calorimetry, and periodically by use of O2 respirometry. The two methods clearly detect diapause termination in both types of pupae before any visible morphological or behavioural changes can be observed. Univoltine individuals are characterized by an increase in metabolic activity from pre‐termination through to termination and post‐termination, ultimately resulting in emergence. Remarkably, a synchronous termination is observed in individuals that enter prolonged diapause instead of emerging; however, in these pupae, the increased metabolic activity is only transient. The present study represents a starting point toward understanding the eco‐physiology of diapause development processes in the pupae of the pine processionary moth. Abstract : The pupae of the pine processionary moth enter a short diapause after which they produce moths, whereas a variable proportion of them enters prolonged diapause. In the present study, changes in metabolic activity are monitored continuously using thermocouples and periodically using O2 respirometry. The two methods clearly detect diapause termination, which is synchronous in both univoltine and prolonged diapause individuals. Increased metabolic activity is only transient in diapausing pupae.